No crepúsculo do voo da ave de Minerva: o(s) fim(ns) da história entre Hegel e o hegelianismo - Dante Alexandre Ribeiro das Chagas (2024)
The end of the dichotomous Cold War inaugurates a New World Order based on US monopolarity with its project of standardization and expansion of the American way of life. A narrative begins that the time of ideologies and utopias has ended in a project that defined neoliberal predatory capitalism as the only possible path across the globe. Neoliberal Globalization tries to impose on the world a project of historical endism that implies the exhaustion of new possibilities and hope. This narrative and project is presented to the world by FRANCIS FUKUYAMA in a perspective, inherited from KOJÈVE, that recovers HEGEL as the philosopher of the end of history and of a universal and homogeneous State. The marriage between historical endism and neoliberalism culminates in a globalization project that attempts to enshrine an abstract cosmopolitanism under the imperialist disguise of exhaustion of alternatives — a historical-neoliberal endism. The objective of our work, therefore, is to understand how the reception of the idea of an end of history occurs in a political-ideological way and implies a certain vision of the State. In a macro-philosophical approach, we seek to reflect on historical endism from HEGEL's Philosophy of History/Philosophy of the State and its appropriations and political-interpretative disputes, having as an arrival point the Hegelian reception of the Jusphilosophical School of Minas Gerais.